Periodic Nonuniform Dynamical Sampling in ℓ2(ℤ) and Shift-Invariant Spaces. (4th March 2017) - Zhang, Qingyue; Li, Rui; Liu, Bei
ABSTRACT: In this article, we mainly study the periodic nonuniform dynamical sampling in ℓ 2 ( ℤ ) and shift-invariant spaces. We first provide a suﬃcient and necessary condition for c ∈ ℓ 2 ( ℤ ) which can be reconstructed by its spatial and temporal samples. Then we give a concrete example to show that the suﬃcient and necessary condition is feasible. Finally, we discuss the periodic nonuniform dynamic sampling problem in shift-invariant spaces.